Tracr Application, Student Lea PENGGUNAAN APLIKASI KHAOOT PADA MATERI GERAK LURUS TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA SWASTA MUHAMMADIYAH 11 PADANGSIDIMPUAN - nasution, seri asmaidah; Siregar, S.Pd., M.Pd, Yenni Amalia (Jurnal Physics Education (PhysEdu), 2024)
The development of science and technology touches almost allof the joints of human life, especially education. In the learning process ofeducation, the learning media is one of the most influential keys to thesuccess of the learning process. The wide range of learning media makeslearning a more varied process. However, the learning media used alsoadjusts the learning model performed. Few students live at home with classconditions carrying out the same learning each day. It is certainly not theresult of students' study. Educators need to encourage learning to becomemore interesting and encourage student interest, thus improving thelearning result. Many societies tend to use technology to search throughthe Internet for information. Furthermore, there are also many societiesthat fill their leisure time with games. Media application Kahoot! Could beone of the alternatives. Khaoot can become a medium of learning andgames with the help of an Internet connection. Khaoot can also raise hisinterest and encourage the digital generation's learning style